2018
DOI: 10.1177/0363546518758298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Predraft Ulnar Collateral Ligament Reconstruction on Future Performance in Professional Baseball: A Matched Cohort Comparison

Abstract: The number of UCL reconstructions performed in amateur baseball players before the draft increased year over year for the entire study period. Professional pitchers who underwent UCL reconstruction as amateurs appear to perform at least as well as, if not better than, matched controls without elbow surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…This finding is likely attributed to MiLB pitchers being generally younger with fewer years of professional baseball experience in comparison with MLB pitchers, such that MiLB pitchers with a history of UCL reconstruction would more likely have undergone surgery before professional play. Additionally, both Camp et al 4 and Wymore et al 19 demonstrated that pitchers with a history of UCL reconstruction as amateurs are increasingly being selected in the MLB draft. This may also contribute to the increased prevalence observed in MiLB from 2012 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is likely attributed to MiLB pitchers being generally younger with fewer years of professional baseball experience in comparison with MLB pitchers, such that MiLB pitchers with a history of UCL reconstruction would more likely have undergone surgery before professional play. Additionally, both Camp et al 4 and Wymore et al 19 demonstrated that pitchers with a history of UCL reconstruction as amateurs are increasingly being selected in the MLB draft. This may also contribute to the increased prevalence observed in MiLB from 2012 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our prior experience, we hypothesized that pitchers undergoing UCLR at a younger age, starting pitchers, pitchers with higher BMIs, and pitchers flagged as moderate and high risk by team physicians would be less successful and have a higher risk for reinjury. We also hypothesized, as concluded by Camp et al, 4 that the surgical cohort would be similarly successful to the matched nonsurgical cohort.…”
mentioning
confidence: 73%
“…In 2016, in a series of 38 pitchers evaluated after UCLR and compared with a control group, Wymore et al 15 demonstrated statistically similar performance metrics between the cohorts in terms of velocity, wins, ERA, WHIP, games started, innings pitched, wins, losses, strikeouts, and batters walked. In 2018, Camp et al 4 conducted a large matched cohort comparison of 345 pitchers after UCLR and demonstrated a statistically higher likelihood of advancement to the MLB level in the UCLR group. Camp et al 4 also found that the postsurgical cohort had a more rapid progression to successive levels of play (such as A, AA, AAA, or MLB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only the impact of UCL reconstruction and shoulder surgery prior to the MLB draft has been investigated, but a macroscopic understanding of the epidemiology and effect on draft rank, availability, and short-term performance remains elusive for all injuries. 3,5,19 The purpose of this study was to determine the (1) epidemiology of all musculoskeletal injuries and surgical procedures among players entering the MLB draft, (2) impact of injury or surgery on draft rank, (3) impact of injury or surgery on availability within the first 2 years of play in the MLB, and (4) impact of injury or surgery on performance. We hypothesized that shoulder and elbow injuries will make up the majority of musculoskeletal injuries in this population and that those who have had prior orthopaedic surgery are likely to be less available or have decreased performance in the MLB.…”
mentioning
confidence: 99%